Potentiometric Studies on Some Ternary Complexes of Uranyl Ion with Pyridine carboxylic Acids and Some Amino Acids - Dongre, V.G.; Janrao, D.M.; Kamble, V.W. (Asian Journal of Chemistry, 2010)
The proton ligand stability constants and stability constants of simple and mixed ligand chelates of uranyl ion with glycine, glycyl-glycine, mercaptopropionyl glycine, α-alanine, β-alanine, aspartic acid, glutamic acid,picolinic, nicotinic and isonicotinic acids have been studied potentiometrically at 25 ± 0.5°C and μ= 0.1 M (NaClO4) in aqueous medium. Uranyl forms 1 : 1 and 1 : 2 complexes with all the chelating agents except in aspartic acid. The mixed ligand chelates are shown to have formed in simultaneous equilibria. The lower values of stability constants of mixed ligand chelates than the sum of the individual log stability constants of the first and second ligand are discussed. The values of the log KMLA for thesystems nicotinidisonicotinic-amino acids have been ascribed to their differencesin the position of the carboxylic group to the pyridine ring, sterichindrance between the ions, size of the chelating agent and electron density of the ring.